2005
DOI: 10.1080/10408360590913533
|View full text |Cite
|
Sign up to set email alerts
|

Bone Disease in Primary Hypercalciuria

Abstract: SummaryPrimary Hypercalciuria (PH) is very often accompanied with some degrees of bone demineralization. The most frequent clinical condition in which this association has been observed is calcium nephrolithiasis. In patients affected by this disorder bone density is very frequently low and increased susceptibility to fragility fractures is reported. The very poor definition of this bone disease from a histomorphometric point of view is a crucial aspect. At present, the most common finding seems to be a low bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 70 publications
0
14
0
2
Order By: Relevance
“…Such a result actually reflects what has already been reported in healthy subjects from our country. (20) Although it is well known that hypercalciuria and secondary hyperparathyroidism can cause osteoporosis, (21) we believe that they do not fully explain the high prevalence of osteoporosis (73%) and vertebral fractures (46%) we observed in our group of PA patients. The expression of mineralcorticoid receptors on bone cells (6) could actually suggest a still unknown direct effect of mineralcorticoids on the skeletal tissue.…”
Section: Discussionmentioning
confidence: 64%
“…Such a result actually reflects what has already been reported in healthy subjects from our country. (20) Although it is well known that hypercalciuria and secondary hyperparathyroidism can cause osteoporosis, (21) we believe that they do not fully explain the high prevalence of osteoporosis (73%) and vertebral fractures (46%) we observed in our group of PA patients. The expression of mineralcorticoid receptors on bone cells (6) could actually suggest a still unknown direct effect of mineralcorticoids on the skeletal tissue.…”
Section: Discussionmentioning
confidence: 64%
“…However, it is generally considered that IH is caused by an alteration in calcium homeostasis at sites where large amounts of calcium must be precisely controlled [5]. Several studies have shown decreased bone mineral density (BMD) in patients with IH [6][7][8][9][10][11][12][13][14][15][16][17][18]. This progressive decrease in bone mineral content suggests that osteoclasts and osteoblasts might play a key role in the chain of events leading to hypercalciuria.…”
Section: Introductionmentioning
confidence: 99%
“…A diet rich in sodium and animal proteins and low in calcium favors the development of calcium lithiasis and the loss of bone mineral density caused by an altered calciumphosphorous metabolism and the appearance of metabolic acidosis. 3,8 A range of studies have demonstrated that relapsing calcium renal lithiasis is associated with bone demineralization, [9][10][11] and calcium renal lithiasis is a risk factor for osteoporotic bone fracture. 12…”
mentioning
confidence: 99%
“…A diet rich in sodium and animal proteins and low in calcium favors the development of calcium lithiasis and the loss of bone mineral density caused by an altered calciumphosphorous metabolism and the appearance of metabolic acidosis. 3,8 A range of studies have demonstrated that relapsing calcium renal lithiasis is associated with bone demineralization, [9][10][11] and calcium renal lithiasis is a risk factor for osteoporotic bone fracture. 12 The objective of this study was to examine and analyze differences in bone remodeling markers, lithogenic factors, and bone densitometry among the 3 groups of patients (controls, patients with relapsing calcium renal lithiasis, and patients with loss of bone mineral density without lithiasis).…”
mentioning
confidence: 99%